PERANAN LINGKUNGAN KERJA DALAM MENINGKATKAN SEMANGAT KERJA PEGAWAI DINAS KEBERSIHAN DAN PERTAMANAN KOTA SAMARINDA - Fatimah, Siti Nur (PREDIKSI, 2012)
The purpose of this study was to determine if the work environment plays a role in improving employee morale and Sanitation Department Landscape Samarinda. To get the data the authors conducted the study. The results showed that the work environment plays an important role in improving employee morale, in the sense that the factor Sanitation Department employee morale and Landscape Samarinda from month to month or from year to year change increase.To improve employee morale, in addition to environmental factors work then another factor needs to be addressed so that the Sanitation Department employee morale and Landscape Samarinda can be improved